Waste management and sustainable economic development in the modern economies - Brankica Todorovic (CES Working Papers, 2019)
The environment is a comprehensive category of the economic development which it should be managed at the level of several policies, including economic and trade policies. Therefore, this paper focuses on: economic and sustainable development according to the indicators Human Development Index (HDI) and Environmental Performance Index (EPI), measures of the economic policies that enable efficient waste management, as well as, the impact of the mass tourism, the growing number of population in cities and development of eco-tourism on the reduction pressures on the environmental.
Keywords: 330; waste management; economic policy; eco-tourism